Methodological Problems of Evidence-Based Description of Psychological and Social Practices - Garifulina E.S; Podushkina T.G; Omelchenko A.S (Moscow State University of Psychology and Education, 2021)
The article offers an analysis of the specifics of the formation of the evidence-based approach in our country. Long-term lack of evidence-based social practices. The entire volume of problems is divided by the authors into two large blocks: a software interface connected to each other. The article examines methodological methods of complexity with the identification of a set of actions necessary and sufficient for changes, a description of the mechanism that constitutes the essence of the intervention, the scientific and theoretical justification of the practice and the complexity associated with the process of collecting and analyzing empirical data on intervention on safe ones. In conclusion, it is concluded that the introduction of an evidence-based approach into the social sphere is an important condition for social practice.